Repetitive injury and absence of monocytes promote astrocyte self‐renewal and neurological recovery. Issue 1 (3rd August 2020) - Lange Canhos, Luisa; Chen, Muxin; Falk, Sven; Popper, Bastian; Straub, Tobias; Götz, Magdalena; Sirko, Swetlana
Abstract: Unlike microglia and NG2 glia, astrocytes are incapable of migrating to sites of injury in the posttraumatic cerebral cortex, instead relying on proliferation to replenish their numbers and distribution in the affected region. However, neither the spectrum of their proliferative repertoire nor their postinjury distribution has been examined in vivo. Using a combination of different thymidine analogs and clonal analysis in a model of repetitive traumatic brain injury, we show for the first time that astrocytes that are quiescent following an initial injury can be coerced to proliferate after a repeated insult in the cerebral cortex grey matter. Interestingly, this process is promoted by invasion of monocytes to the injury site, as their genetic ablation (using CCR2 −/− mice) increased the number of repetitively dividing astrocytes at the expense of newly proliferating astrocytes in repeatedly injured parenchyma. These differences profoundly affected both the distribution of astrocytes and recovery period for posttraumatic behavior deficits suggesting key roles of astrocyte self‐renewal in brain repair after injury. Main Points: Repetitive injury activates proliferation of previously quiescent astrocytes. Reactive astrocytes can proliferate repeatedly. Lack of monocytes promotes cell cycle re‐entry of astrocytes at the injury site and neurological recovery.